Digital technologies are the basis of digital economy of civil aviation airport refueling complexes - A. A. Brailko; O. V. Gromov; L. A. Druzhinin (Научный вестник МГТУ ГА, 2020)
The article analyzes the main information automated control systems for refueling complexes, based on this analysis, the problems of the airport ground handling functioning are identified, the main of which are the inefficiency of managing stochastic processes that occur in failure situations, as well as the lack of automated control systems for the level of purity of aviation fuel from mechanical impurities and water. The way to upgrade Groundstar Inform GmbH - a single integrated airport management system by increasing the capabilities of the system by adding new components is proposed. A solution to the problem of multi-resource planning of aircraft refueling in high-intensity flight conditions, including failure situations, based on intelligent simulation and resource management is proposed. As well as from the point of view of optimizing the solution of business process objectives the development of planning algorithms using the mathematical apparatus of fuzzy modeling and control, fuzzy sets and fuzzy logic underlying the intelligent modeling of processes is proposed. The concept of an adaptive information management system of technological processes of a refueling complex for monitoring the purity of jet fuel, based on dynamic on-line monitoring of the existence of mechanical impurities and water is introduced. The article examines the elements of creating a "Smart Refueling Complex", in which intelligent business processes are combined into one whole due to the use of "smart" operational processes and technological equipment. The introduction of digital technologies, "industry 4.0" tools and trends in automation, digitalization and digitalization of the modern aviation fuel supply for civil aviation is becoming the basis of the digital economy of civil aviation refueling complexes.